HUBUNGAN PERKEMBANGAN PRODUKSI KAKAO TERHADAP PERTUMBUHAN EKONOMI MASYARAKAT DI DESA BATUAH - Muhammad Refliansyah; Bulkis (Jurnal Cakrawala Ilmiah, 2024)
Cocoa is a commodity that is not only of significant economic value but also plays a critical role in the overall economy of Indonesia. Batuah Village is one of the regions in Indonesia that is recognised as a cocoa centre. The purpose of this investigation is to determine whether there is a correlation between the economic development of the Batuah Village community and the development of cocoa production. Multiple linear regression analysis techniques are implemented in the quantitative research methodology. The study's data was collected through firsthand surveys of 10 cocoa farmers in Batuah Village. The results of this investigation suggest that the economic development of the Batuah Village community is substantially affected by cacao production. A positive correlation between cacao production and monthly income, as well as other economic variables, is demonstrated by regression analysis. Furthermore, cocoa prices, market access, and capital access are additional variables that affect economic growth. The expansion of cocoa production not only increases the income of farmers but also generates new employment opportunities and fosters the development of village infrastructure. This promotes economic expansion and enhances the well-being of the community.